Identifying and Mitigating Web Application Vulnerabilities: A Comparative Study of Countermeasures and Tools - Sadat, Sayed Elham; Naseri, Mohammed Fahim; Salamzada, Khosraw (International Journal Software Engineering and Computer Science (IJSECS), 2024)
In the current age of technology, web applications and websites have experienced significant growth. This expansion has made their security a critical area of research. Web applications offer benefits, which makes user’s lives easier. In this paper, common web application vulnerabilities and effective strategies to mitigate the vulnerabilities are identified using a comparative study of countermeasures and open-source web application vulnerability assessment tools. Specifically, the top ten web application vulnerabilities and their countermeasures are investigated. Accordingly, several open-source vulnerability assessment tools are also introduced. The review highlights that with the developments and deployments of web applications on the internet, users are chased by a remarkable number of cyber-attacks. Attackers take advantage of available vulnerabilities in a web application or website, such as SQL injections, cross-site scripting, and broken authentications. This paper concludes by providing the best practices to mitigate cyber-attacks on web applications and suggests future directions for enhancing vulnerability assessment through machine learning techniques